Finite-time event-triggered non-fragile control and fault detection for switched networked systems with random packet losses. Issue 16 (November 2020) - Liu, Yurong; Arunkumar, A.; Sakthivel, R.; Nithya, V.; Alsaadi, F.
Abstract: This paper investigates the problem of event-triggered observer-based fault detection for a class of uncertain switched nonlinear network control systems (SNNCSs) with random communication packet losses and infinite distributed delay. The main objective of this work is to design an event-triggered state feedback non-fragile H ∞ controller such that the resulting closed-loop form of the considered SNNCSs is robustly finite-time bounded and satisfies a prescribed H ∞ performance constraint in the finite-time interval. By employing average dwell time approach, the problem of finite-time boundedness and residual H ∞ performance analysis is discussed. Specifically, a new set of conditions in the form of LMIs are derived to ensure the finite-time boundedness with the prescribed residual H ∞ performance for the relevant closed-loop system. Moreover, the desired observer-based state feedback controller gain matrices and residual weighting matrices can be expressed in an explicit form. Finally, the applicability and effectiveness of the developed results are examined via numerical examples with simulation results.